23. PATIENT SATISFACTION AND ASSOCIATED FACTORS IN POSTOPERATIVE CARE AMONG INPATIENTS AT TRANSPORT HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2026)
Objective: To assess patient satisfaction with postoperative care and analyze associated factors among inpatients at Transport Hospital in 2024.Methods: A cross-sectional descriptive study was conducted on 210 postoperative inpatients at Transport Hospital between January and December 2024. Data were collected using a standardized patient satisfaction questionnaire and analyzed with SPSS, applying descriptive statistics and Chi-square tests to identify significant associations.Results: Overall satisfaction rate was 86.7%. Significant factors associated with satisfaction included length of hospital stay (p